1991
DOI: 10.2500/105065891781976818
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nasal Polyps by Steroid Nose Drops

Abstract: Systemic steroids may remove symptoms from nasal polyps in most patients, while surgery only is necessary in a few resistant cases. However. topical medication is preferable. Sprays may prevent recurrencies, but they seldom suffice for removing polyps. The aim of the present study was to document clinical efficacy of steroid nose drops. In 24 patients with nasal polyps documented by mini biopsy, aqueous budesonide (Rhinocort Aqua. Draco. Sweden) was applied as nose drops. Every second day 0.25 ml was instilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Topical application of corticosteroids dramatically reduces the risk of systemic side effects [107]. Many studies have demonstrated the safety and efficacy of INS in nasal polyposis even if the intrasinus portion of the polyps is not reachable with a nasal spray [108][109][110][111][112]. Among all the specialities, mometasone furoate and fluticasone furoate are the newest and safest molecules with the lowest bioavailability.…”
Section: Chronic Rhinosinusitis With Nasal Polypsmentioning
confidence: 99%
“…Topical application of corticosteroids dramatically reduces the risk of systemic side effects [107]. Many studies have demonstrated the safety and efficacy of INS in nasal polyposis even if the intrasinus portion of the polyps is not reachable with a nasal spray [108][109][110][111][112]. Among all the specialities, mometasone furoate and fluticasone furoate are the newest and safest molecules with the lowest bioavailability.…”
Section: Chronic Rhinosinusitis With Nasal Polypsmentioning
confidence: 99%
“…Administration of corticosteroids is considered an established first‐line treatment in nasal polyposis 6,7 . Treatment with topical or systemic corticosteroids reduces the volume of small polyps and may prevent or delay the recurrence of polyps after their endonasal surgical removal 8‐11 .…”
Section: Introductionmentioning
confidence: 99%